2013
DOI: 10.1021/cm302680j
|View full text |Cite
|
Sign up to set email alerts
|

Rational Design of Nickel Phosphide Hydrodesulfurization Catalysts: Controlling Particle Size and Preventing Sintering

Abstract: The size-dependent catalytic activity of Ni 2 P for hydrodesulfurization (HDS) remains unstudied because the traditional temperature programmed reduction (TPR) method used in catalyst preparation results in highly polydisperse Ni 2 P particles. The ability to control the Ni 2 P particle size in the range 5−20 nm by varying the quantity of oleylamine in solution-phase arrested precipitation reactions is reported. Particles were introduced to a high surface area silica support (Cab-O-Sil, M-7D grade, 200 m 2 /g)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
74
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(80 citation statements)
references
References 31 publications
3
74
1
Order By: Relevance
“…For example, nanoparticles of Ni 2 P, Ni 12 P 5 , and Ni 5 P 4 show contrasting performances in the HER . Broadly, a good understanding of the surface chemistry of metal phosphides produced by colloidal routes is essential to their development in other branches of catalysis, for example, hydrotreatment and selective hydrogenation reactions …”
Section: Introductionmentioning
confidence: 99%
“…For example, nanoparticles of Ni 2 P, Ni 12 P 5 , and Ni 5 P 4 show contrasting performances in the HER . Broadly, a good understanding of the surface chemistry of metal phosphides produced by colloidal routes is essential to their development in other branches of catalysis, for example, hydrotreatment and selective hydrogenation reactions …”
Section: Introductionmentioning
confidence: 99%
“…), solution-phase arrestedprecipitation reactions enable excellent control of size, shape and composition, producing samples comprising narrowly polydisperse, discrete nanoparticles. [18][19][20][21] This approach has been extensively employed for the synthesis of binary phosphides, and these have recently been demonstrated to be effective as model catalysts for HDS 22,23 as well as electrocatalysts for HER. [6][7][8][9][10] In contrast, few examples of arrested precipitation reactions delivering ternary phosphide nanoparticles are reported.…”
Section: Introductionmentioning
confidence: 99%
“…35 Initially thought to be a semiconductor, electronic structure calculations revealed that bulk Ni 2 P is actually metallic. 36,37,38 Interestingly, their resemblance to noble metals goes well beyond HER, as first row transition metal phosphides are also active catalysts in hydrotreating (HDX, X = S or hydrodesulfurization, 39,40,41,42 O or hydrodeoxygenation 43,44,45 , and N or hydrodenitrogenation 46,47 ), alkyne hydrogenation, 48,49,50,51 and hydrodearomatization reactions. 52 The ability of Ni 2 P and other Earth-abundant, binary metal phosphides to readily and reversibly adsorb hydrogen (H 2 ), perform a wide range of hydrogenation-like reactions, and achieve high product selectivities strongly suggest that they could also catalyze the hydrogenation of other, typically more challenging reactants, such as nitrate (NO 3 -).…”
Section: Introductionmentioning
confidence: 99%